Effect of dwell period on fatigue life of 316l stainless steel tube at high temperature under creep condition - Mohammad, Khairul Azhar (2014)
Components of engineering structures that operate at high temperatures, such as jet engines, pressure vessels, nuclear reactors, oil and gas plants, and steam and gas turbines, are subjected to significant thermal and mechanical loadings. As the external surfaces of structures always maintain contact with the environment and are exposed to weather, surface cracks may form due to imperfections during product fabrication. The main purpose of this study was to characterize and examine the relative importance of the mechanism of fatigue damage in tubular structures, which occur at high temperatures, and to develop an adaption equation of creep-fatigue life prediction based on failure mechanisms at high temperatures. In this study, a 316L stainless steel grade tubular structure was employed to characterize the prediction fatigue lifetime of plant industry components at operating temperatures in the range of 500-650°C and in creep-fatigue loading conditions. Fatigue tests were performed in the finite life region of a rounded specimen with a constant load amplitude, a constant frequency of 5 Hz and the stress ratio R of 0.1 at room temperature. A constant load and high temperature of 565°C were imposed on the specimen during the creep test. The nature of a hold period (tensile or compressive) affects fatigue life and surface crack patterns. The creep-fatigue test, which is similar to the fatigue test, with five hold times at maximum tensile stress, was conducted using a rounded specimen of “Type 316L stainless steel” at 565°C. Optical and scanning electron microscopy was performed to characterize the metallurgical damage and explain the microscopic damage mechanics. Fatigue tests with and without hold periods were performed to assess the influence of creep-fatigue interaction on fatigue life. The results of the tests indicated that creep and temperature significantly impact fatigue behaviour. In several cases, fatigue lives were significantly reduced with an applied hold time at high temperatures. Hold times are most damaging at high stress ranges and low fatigue lives. Many parameters affect the fatigue performance of structural components. Fatigue life is influenced by a variety of factors, such as the geometries and properties of specimens, stress, temperature, surface finish, direction of loading, presence of oxidizing or inert chemicals. Fatigue with a hold time and fatigue without a hold time at the fatigue limit were determined to be 39.2 MPa and 87.8 MPa, respectively, in this research. The fatigue life of the 316L stainless steel was estimated by approaching the mean stress using a continuum damage mechanism (CDM). The continuum damage mechanism provides a reasonable prediction of fatigue response for high conditions. Based on the observation and characterization of fatigue life tubular steel pipes, the adaption equation for creep fatigue life prediction was proposed. Its simplicity gives it credibility and the adjustable use of alloy metal, which incorporates a number of cycles, applied stress and temperature, enables a power plant to predict the fatigue life of engineering components. The adaption equation can facilitate the damage tolerance design, which is the best design approach for reducing the cost and weight of heavy applications in the manufacturing process. A damage tolerant design philosophy for creep has been previously developed to improve the creep properties and elevated temperature fatigue crack growth resistance without sacrificing tensile strength and Low Cycle Fatigue (LCF) crack initiation life relative to the conventional microstructure (CM). Understanding the fatigue behaviour of steel pipes, which are derived from this study, are also useful in the design stage. To validate the experimental results, the fatigue life prediction using finite element analysis (FEA) via Abaqus was employed. The simulation was performed by applying different stress levels to predict the stress of operation to measured life at the measured operation stress. The focus of the simulation is the importance of characterizing the fatigue limit using a comparison with experimental data. The fatigue limits for the simulation and the experiment are 150 MPa and 161 MPa, respectively, which correspond in terms of accuracy prediction; various aspects should be considered in the simulation. Additional developments in the analysis of creep-fatigue prediction test data are discussed, and expression for estimating fatigue life at high temperatures in stress-controlled tests are derived. To check the validity of adaption model proposed in this study, the assessment for creep fatigue interaction tests of austenitic 316L stainless steel under stress control at 565oC has been conducted. The life prediction results are within a factor of   1.5, which indicates that the model is suitable for stress-controlled fatigue or creep fatigue life prediction of ductile material. The predicted results correspond with the experimental data.